ANALISIS MASLAHAH TERHADAP FATWA MUI SUMENEP TENTANG PROFESI MENGEMIS - Fitria, Norma (Irtifaq, 2015)
Profession of beggars causes mental damage to the moral order and the whole of society, ranging from adults to small children. Majelis Ulama Indonesia (MUI) has issued a fatwa about the prohibition of beggars. The concept of ‚Mas}lah{ah‛ to the Fatwa of MUI Sumenep on the prohibition of the profession of beggars aims to find out how MUI formulated methodological ushul rules of fiqh of language by testing against is adillah al-ahka>m used by MUI and how the fatwa correlation with maqa>s}id al-shari>'ah approach of rules of Ushul Fiqh. From the analysis, it can be understood that all the arguments of law used in the fatwa of MUI, beggar profession can be argued as to establish a law with permanent legal of force and binding. Besides, the fatwa is also very relevant to maqa>s}id al-shari>'ah in which aims to bring serious benefits and avoid mafsadat in human life. Keywords: Mas}}lah}ah, Fatwa MUI, Beggars